Prevalence of Stafne's Cyst - A retrospective analysis of 18,040 Orthopantomographs in Western India - Sugandha Arya; Ashish Pilania; Jitender Kumar (Wolters Kluwer Medknow Publications, 2019)
Introduction: Stafne's cyst (SC) is a bone depression found on the lingual side of the mandible. It is a sharply demarcated osteolytic lesion of the mandible, caudal to the inferior alveolar nerve and restricted to the regions of the molars and mandibular angle. Purpose: Stafne's bone cyst is usually asymptomatic being diagnosed on the routine radiographs as an incidental finding hence, its actual prevalence is unknown. Moreover, the lesion simulates many odonogenic pathologies thereby, and the entity remains a diagnostic challenge. So, the present study was conducted to investigate the prevalence of SC in Jodhpur population of Western India. Materials and Methods: A retrospective analysis of 18040 OPGs was done on the basis of diagnostic criteria described by Stafne. Results: A total of 6 cases fulfilled diagnostic criteria of SC (0.03%), 4 cases were reported in men (66.6%), at a mean age of 50.75 years, and 2 cases in women (33.3%), at a mean age of 31.5 years. Involvement of SC on left and right side of the mandible was given as 4:2 in ratio. All 6 cases of SC was found in the body of mandible (100%). Rare case of double unilateral form of SC was reported in 1 patient. Conclusion: Orthopantomographs (OPGs) may ensure initial opinion regarding the diagnosis of SC and alert the clinicians to exclude other potential pathologies to avoid invasive procedures.